2019
DOI: 10.1002/uog.20346
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of impaired placentation at 35–37 weeks' gestation in the prediction of adverse perinatal outcome

Abstract: Objective To investigate the potential value of uterine artery pulsatility index (UtA‐PI) and serum levels of the angiogenic placental growth factor (PlGF) and the antiangiogenic factor soluble fms‐like tyrosine kinase‐1 (sFlt‐1) in the prediction of adverse perinatal outcome in small‐for‐gestational‐age (SGA) and non‐SGA neonates at 35–37 weeks' gestation. Methods This was a prospective observational study of 19 209 singleton pregnancies attending for a routine hospital visit at 35 + 0 to 36 + 6 weeks' gestat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…24,26 Although low maternal PlGF levels in the third trimester have been shown to be associated with IFC and adverse neonatal outcomes, 148,149 the evidence is conflicting with another recent study, suggesting that it did not predict cesarean birth for fetal compromise. 150 Identification of intrapartum fetal compromise Despite concerted efforts to develop accurate techniques for the identification of intrapartum fetal hypoxia, to date all techniques currently in clinical practice have poor positive predictive values. 151 Reviews of conventional antepartum cardiotocography (CTG), computerized FHR analysis, or intermittent auscultation have concluded that they do not result in improved perinatal outcomes.…”
Section: Figurementioning
confidence: 99%
“…24,26 Although low maternal PlGF levels in the third trimester have been shown to be associated with IFC and adverse neonatal outcomes, 148,149 the evidence is conflicting with another recent study, suggesting that it did not predict cesarean birth for fetal compromise. 150 Identification of intrapartum fetal compromise Despite concerted efforts to develop accurate techniques for the identification of intrapartum fetal hypoxia, to date all techniques currently in clinical practice have poor positive predictive values. 151 Reviews of conventional antepartum cardiotocography (CTG), computerized FHR analysis, or intermittent auscultation have concluded that they do not result in improved perinatal outcomes.…”
Section: Figurementioning
confidence: 99%
“…In this sense, it seems reasonable that multiple parameters should be assessed for better prediction of fetuses at risk of stillbirth 43,45,46 . Although the use of biomarkers such as placental growth factor and sFlt1 has proved useful in the prediction and timely diagnosis of pre‐eclampsia, 47,48 in pregnancies at 35–37 weeks of gestation, the routine assessment of these markers provided poor prediction of perinatal outcomes in both SGA and non‐SGA fetuses 49 . Maybe the incorporation of these markers to more comprehensive algorithms should be the key to a better predictive performance regarding SGA and term stillbirth.…”
Section: Management Of Late‐onset Fgrmentioning
confidence: 99%
“…Indeed, growth restriction can account for up to half of the fetal deaths of unknown causes [54], being about 6-fold higher than the chance of stillbirth at term (relative risk, RR, 6.0; 95% CI, 3.1–11.5) [11], or when the birthweight is <5 th percentile (compared to the 10–90 th centiles) [17]. Besides perinatal death [6, 11, 12, 1518, 55], preterm birth [6, 11, 14], and other short-term adverse events are described for SGA infants (Table 1); the adjusted odds ratio (aOR) for composite neonatal morbidity can be as high as 3.22 (95% CI, 3.07–3.39) [12]. Interestingly, SGA suspicion in pregnancy is associated with better neonatal outcomes [18, 57], which turns SGA screening a cornerstone strategy for reducing antepartum fetal loss [13, 58] and meliorating neonatal morbidity ratios.…”
Section: Why We Should Screen For Fetal Growth Restriction?mentioning
confidence: 99%